2012
DOI: 10.1155/2012/236217
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Disturbances and Quality of Life in Obese and Infertile Women and Men

Abstract: Anovulatory cycles and endometriosis are the main causes of female infertility. The most frequently anovulatory cycles are related to polycystic ovary syndrome (PCOS) commonly associated with obesity and hormonal disturbances in the course of obesity. Recently published studies revealed that infertility affects about one in six couples during their lifetime and is more frequent in obese. Obesity is also associated with male infertility related to erectile dysfunction, hormonal disturbances and lower semen qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 190 publications
(212 reference statements)
0
15
0
7
Order By: Relevance
“…Clinical symptoms of PCOS and accompanying disorders, especially hirsutism, acne and excessive weight, are socially and culturally defined as unfeminine and undesirable, so women with PCOS may feel themselves to be less attractive. Increased androgen level also seems to have some impact on mood disorders [2].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical symptoms of PCOS and accompanying disorders, especially hirsutism, acne and excessive weight, are socially and culturally defined as unfeminine and undesirable, so women with PCOS may feel themselves to be less attractive. Increased androgen level also seems to have some impact on mood disorders [2].…”
Section: Introductionmentioning
confidence: 99%
“…Infertility may not be a threat to physical health but carries with it extremely adverse social and psychological implications for all concerned but particularly in developing countries. A review article reported that there is significant association between obesity and infertility and psychological disturbances as well as their impact on quality of life and sexual functioning in women and men 5 . Since it is accepted that individuals cannot achieve health in general and reproductive health in particular without the alleviation of infertility, there is an ever-increasing need and urgency to develop simple, low-cost, and effective modalities for evaluation, treatment, and prevention of infertility, which can be applied universally 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Infertilnost je, kao i gojaznost, faktor rizika za psihološke poremećaje i lošiji kvalitet života u populaciji žena i muškaraca reproduktivnog doba. S druge strane, poremećaji raspoloženja mogu dovesti do hormonalne disfunkcije i smanjiti efikasnost lečenja infertiliteta [Kocełak 2012]. Mnogu pacijenti koji imaju probleme sa fertilitetom traže medicinsku pomoć i onima sa perzistentnim problemima omogućava se lečenje metodama asistirane reprodukcije.…”
Section: Diskusija Studije Determinanti Zdravstvenogunclassified